2017
DOI: 10.3390/molecules22071095
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, Mechanism and Theoretical Studies of Norbornene-Ethylene Alternating Copolymerization Catalyzed by Organopalladium(II) Complexes Bearing Hemilabile α-Amino–pyridine

Abstract: Cationic methylpalladium complexes bearing hemilabile bidentate α-amino–pyridines can serve as effective precursors for catalytic alternating copolymerization of norbornene (N) and ethylene (E), under mild conditions. The norbornyl palladium complexes in the formula of {[RHNCH2(o-C6H4N)]Pd(C7H10Me)(NCMe)}(BF4) (R = iPr (2a), tBu (2b), Ph (2c), 2,6-Me2C6H3 (2d), 2,6-iPr2C6H3 (2e)) were synthesized via single insertion of norbornene into the corresponding methylpalladium complexes 1a–1e, respectively. Both squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 114 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Chen et al and Suslov et al evaluated Pd complexes bearing a hemilabile bidentate α-amino-pyridine moiety (Pd90 and Pd91, Figure 19) in norbornene polymerization. [88,89] Acetylacetonate Pd complexes (Pd91) did not catalyze the VAP of NB without a cocatalyst. However, oligomerization of NB was observed in the presence of methylpalladium complexes with a labile MeCN ligand (Pd90).…”
Section: Palladium Complexes Containing Chelate Bidentate Nnligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al and Suslov et al evaluated Pd complexes bearing a hemilabile bidentate α-amino-pyridine moiety (Pd90 and Pd91, Figure 19) in norbornene polymerization. [88,89] Acetylacetonate Pd complexes (Pd91) did not catalyze the VAP of NB without a cocatalyst. However, oligomerization of NB was observed in the presence of methylpalladium complexes with a labile MeCN ligand (Pd90).…”
Section: Palladium Complexes Containing Chelate Bidentate Nnligandsmentioning
confidence: 99%
“…Considering the possible ways of linking norbornene units, three types of such links are expected: exoexo-, endo-endo-, and exo-endo-enchainment (Figure 25a-C). Xray analysis of both intermediates with inserted norbornene molecule(s) into the metalÀ C bond [46,55,74,[82][83]86,88] and crystalline oligomers of norbornene derivatives [94] obtained in VAP clearly indicated exo-exo-linking of norbornene units. No experimental proof of endo-endo-or exo-endo-linking of norbornene units has been reported thus far.…”
Section: Chain Propagation Step Of Vapmentioning
confidence: 99%
“…N−N-and N−O-ligated cationic Pdcomplexes of a similar structure were found to be singlecomponent catalysts for VAP of unsubstituted norbornenes. 51,52 Chen and co-workers showed that a zwitterionic phospine-sulfonate Ni-complex is a latent catalyst for norbornene polymerization. 53 Recently, Peŕez-Ortega and Albeniz reported cationic benzylic Pd-complexes as onecomponent catalysts for VAP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The rigid repeat unit can contribute to useful physical properties 24,25 . Copolymerization of norbornene with ethylene or propylene initiated by metal complexes affords cyclic olefin copolymers with unique properties 26,27 . Furthermore, norbornenes have been copolymerized with methacrylates to achieve useful optical properties 25 …”
Section: Introductionmentioning
confidence: 99%